2021
DOI: 10.1177/13684302211020108
|View full text |Cite
|
Sign up to set email alerts
|

Love thy (partisan) neighbor: Brief befriending meditation reduces affective polarization

Abstract: The rising partisan animus between Democrats and Republicans has significant consequences for American society, both political and nonpolitical. The present study used two preregistered randomized controlled designs to investigate whether scalable meditation interventions could reduce affective polarization, relative to baseline scores measured 1 week earlier, in American adults (Study 1: N = 353; Study 2: N = 246) who affiliated with either the Democratic Party or the Republican Party. The results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
2
15
1
Order By: Relevance
“…It suggests that sustained mindfulness training may be an effective intervention to reduce affective polarization, at least modestly. Importantly, in contrast to studies testing meditation inductions on affective polarization (e.g., Simonsson et al, 2021), these effects were observed outside the context of meditation practice. This supports the possibility that meditation training may lead to sustained and generalized changes in attitudes toward outgroup members.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…It suggests that sustained mindfulness training may be an effective intervention to reduce affective polarization, at least modestly. Importantly, in contrast to studies testing meditation inductions on affective polarization (e.g., Simonsson et al, 2021), these effects were observed outside the context of meditation practice. This supports the possibility that meditation training may lead to sustained and generalized changes in attitudes toward outgroup members.…”
Section: Discussioncontrasting
confidence: 66%
“…Results from previous research have shown that 10 min of befriending meditation reduced affective polarization in American adults who affiliated with either the Democratic Party or the Republican Party (Simonsson et al, 2021). While promising, effects in these studies were modest in magnitude (ds ≤ 0.31).…”
mentioning
confidence: 63%
“…One notable exception is research assessing the effect of a short mindfulness intervention on affective political polarization in the US (Simonsson et al, 2021). Results are ambiguous, however: while a brief befriending meditation-an essential ingredient in mindfulness courses-reduces affective polarization between Democrats and Republicans by increasing positive feelings for the outgroup, no similar effect was detected for a mindfulness meditation intervention.…”
Section: Extant Research At the Mindfulness-politics Nexusmentioning
confidence: 99%
“…Research suggests that antecedent-focused strategies of emotion regulation, such as positive re-appraisal, are positively related to political liberalism (Lee et al, 2013), pro-sociality , and political tolerance across group boundaries (Halperin et al, 2014). With induced mindfulness engendering increases in positive reappraisal (Garland et al, 2011), scholars interested in conflict resolution and political polarization are encouraged to follow the pathway set out by Alkoby et al (2017) and Simonsson et al (2021) to further explore the potential of mindfulness for inter-group reconciliation.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…In the context of planetary health and unprecedented biodiversity losses, the latter would seem to be an important consideration. In a brief LKM-like intervention (referred to as befriending meditation), the practice has been shown to reduce affective polarization between Democrats and Republicans by increasing positive feelings relatively more for the political outgroup than the political ingroup [107]. Preliminary research shows that among its potential benefits, LKM increases mindfulness [108].…”
mentioning
confidence: 99%